REVIEW : POTENSI PENGGUNAAN BAHAN ALAM SEBAGAI TERAPI KOMPLEMENTER ALTERNATIF PADA PENDERITA DEMAM BERDARAH DENGUE (DBD) - Fitri Aida; Salman Salman; Indah Laily Hilmi (Journal of Pharmaceutical and Sciences, 2023)
DHF (Dengue Hemorrhagic Fever) is a disease that frequently occurs in tropical and subtropical climates. This disease is caused by infection with dengue virus (DENV) through the bite of the Aedes aegypty or Aedes albopictus mosquito as the primary vector. The death rate for DHF cases in Indonesia since January 2022 has increased by 89 cases compared to 2020. The main factors causing death in DHF cases are platelet deficiency and plasma leakage, which are not immediately treated. The main principle in managing DHF (Dengue Hemorrhagic Fever) is symptomatic therapy and supportive therapy, such as raising the platelet count. This study aimed to find various natural ingredients that have the potential as complementary therapies in patients with dengue hemorrhagic fever (DHF). The method used was a literature review. The results obtained were red dragon fruit skin (Hylocereus polyrhizus), sweet potato leaves (Ipomoea batatas. L), god leaves (Gynura pseudochina (L), black turmeric rhizome (Curcuma aeruginosa Roxb.), horsetail fern leaves (Equisetum hyemale), date fruit (Phoenix dactylifera), bark of Chinese castor oil (Jatropha multifida), papaya leaves (Carica papaya L), patikan kebo leaves (Euphorbia hirta), guava leaves (Psidium guajava), Wegio nutmeg (Myristica fatua) , and Sambiloto leaves (Andrographis paniculate) have the potential as a complementary therapy in DHF patients